2009
DOI: 10.1111/j.1365-2214.2009.00942.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical, motor, sensory and developmental features associated with agenesis of the corpus callosum

Abstract: These results extend previous descriptions but are also consistent with published reports that used small samples and single case studies. The data provide a profile that has implications for early detection and intervention of individuals with ACC as well as for highlighting future research directions to extend knowledge about ACC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 42 publications
3
34
1
2
Order By: Relevance
“…As hypothesized, proportionately more participants with AgCC than the normative sample endorsed low registration of sensory experience in both levels of analysis—Atypically High (> 1 SD) and Definitely High (> 2 SD). These results are consistent with previous research in which individuals with AgCC were reported to have high pain tolerance (Doherty et al, 2006; Moes et al, 2009), or “low registration” for pain sensation. Current results suggest that this high tolerance for pain may be related to a higher threshold for detection of pain or slower response to painful input.…”
Section: Discussionsupporting
confidence: 92%
“…As hypothesized, proportionately more participants with AgCC than the normative sample endorsed low registration of sensory experience in both levels of analysis—Atypically High (> 1 SD) and Definitely High (> 2 SD). These results are consistent with previous research in which individuals with AgCC were reported to have high pain tolerance (Doherty et al, 2006; Moes et al, 2009), or “low registration” for pain sensation. Current results suggest that this high tolerance for pain may be related to a higher threshold for detection of pain or slower response to painful input.…”
Section: Discussionsupporting
confidence: 92%
“…Six cases were nonspecific; of which Three had isolated ventriculomegaly and the other Three had delayed myelination. Moes et al, [13] also observed similar incidence of Degenerative/ Metabolic Diseases causing developmental delay.…”
Section: Discussionmentioning
confidence: 63%
“…In light of the functional specialization of the insula, diminished connectivity in the anterior insula from the ICA analysis may indicate that AgCC has a significant effect on the anterior insular network, including the anterior cingulate cortex, middle/inferior frontal cortex, temporoparietal network, and their related functions, that is, emotional salience and attentional control. Individuals with AgCC are known to have diminished pain sensitivity and altered emotional processing (Moes et al, 2009). This corresponds with the insula's prominent role as a center of the ''pain network,'' particularly as a convergence zone for the affective and sensory components of pain (Augustine 1996;Vanhaudenhuyse et al, 2009).…”
Section: Functional Specialization Of the Insulamentioning
confidence: 99%